2013
DOI: 10.11114/jets.v1i2.94
|View full text |Cite
|
Sign up to set email alerts
|

Using Action Verbs as Learning Outcomes: Applying Bloom’s Taxonomy in Measuring Instructional Objectives in Introductory Psychology

Abstract: We used a set of action verbs based on Bloom's taxonomy to assess learning outcomes in two college-level introductory psychology courses. The action verbs represented an acronym, IDEA, comprising skills relating to identifying, defining or describing, evaluating or explaining, and applying psychological knowledge. Exam performance demonstrated that higher level cognitive skills in Bloom's taxonomy represented by the action verbs evaluating and explaining were the most difficult for students to acquire and also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
1
11
0
2
Order By: Relevance
“…As expected, students performed better overall on lower level questions (basic definitions and content knowledge) than on higher level questions that required cognitive skills relating to application, analysis, and explanation. Previous research has shown that exam questions that tap into more complex cognitive skills in Bloom’s taxonomy have higher difficulty levels than questions assessing lower level cognitive skills (Nevid & McClelland, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As expected, students performed better overall on lower level questions (basic definitions and content knowledge) than on higher level questions that required cognitive skills relating to application, analysis, and explanation. Previous research has shown that exam questions that tap into more complex cognitive skills in Bloom’s taxonomy have higher difficulty levels than questions assessing lower level cognitive skills (Nevid & McClelland, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Representasi kata kerja dalam buku teks mempertegas luaran pembelajaran (Stanny, 2016). Satu level kognitif dapat dipertegas dengan berbagai macam kata kerja, sehingga capaian kemampuan kognitif yang tinggi tidak merepresentasikan kemampuan seluruh bentuk aktivitas yang tercakup di dalamnya (Nevid and McClelland, 2013). Penggunaan kosakata dalam buku teks seharusnya disesuaikan dengan tingkatan pendidikan.…”
Section: Pembahasanunclassified
“…Student competency in the course's learning outcomes was measured by adopting the Bloom's (1956) taxonomy which represents the hierarchy of skills development on expected outcomes such as knowledge, comprehension and application. To measure the skills at different levels of cognitive complexity and higher-order skills, which particularly require more sophisticated cognitive processes (Crowe, Dirks, & Wenderoth, 2008;Nevid & McClelland, 2013), competency on course learning outcomes was measured by a series of multiple-choice exams, grouped according to Bloom's taxonomy (memory, understanding, and apply) to be able to develop a reliable and valid assessment (Haladyna, 1999). Each group on Bloom's taxonomy had eleven questions; and each memory items on learning outcomes was scored as two points, understanding items were awarded three points, and apply items were awarded four points.…”
Section: Competencies In Learning Outcomesmentioning
confidence: 99%